SINEUPs: a novel toolbox for RNA therapeutics. Issue 4 (27th October 2021) - Espinoza, Stefano; Bon, Carlotta; Valentini, Paola; Pierattini, Bianca; Matey, Abraham Tettey; Damiani, Devid; Pulcrano, Salvatore; Sanges, Remo; Persichetti, Francesca; Takahashi, Hazuki; Carninci, Piero; Santoro, Claudio; et al.
Abstract: RNA molecules have emerged as a new class of promising therapeutics to expand the range of druggable targets in the genome. In addition to 'canonical' protein-coding mRNAs, the emerging richness of sense and antisense long non-coding RNAs (lncRNAs) provides a new reservoir of molecular tools for RNA-based drugs. LncRNAs are composed of modular structural domains with specific activities involving the recruitment of protein cofactors or directly interacting with nucleic acids. A single therapeutic RNA transcript can then be assembled combining domains with defined secondary structures and functions, and antisense sequences specific for the RNA/DNA target of interest. As the first representative molecules of this new pharmacology, we have identified SINEUPs, a new functional class of natural antisense lncRNAs that increase the translation of partially overlapping mRNAs. Their activity is based on the combination of two domains: an embedded mouse inverted SINEB2 element that enhances mRNA translation (effector domain) and an overlapping antisense region that provides specificity for the target sense transcript (binding domain). By genetic engineering, synthetic SINEUPs can potentially target any mRNA of interest increasing translation and therefore the endogenous level of the encoded protein. In this review, we describe the state-of-the-art knowledge of SINEUPs and discuss recent publications showing their potential application in diseases where a physiological increase of endogenous protein expression can be therapeutic.